The benefit to waitlist patients in a national paired kidney exchange program: Exploring characteristics of chain end living donor transplants. Issue 1 (17th July 2021) - Osbun, Nathan; Thomas, Alvin G.; Ronin, Mathew; Cooper, Matthew; Flechner, Stuart M.; Segev, Dorry L.; Veale, Jeffrey L.
Abstract : Nondirected kidney donors can initiate living donor chains that end to patients on the waitlist. We compared 749 National Kidney Registry (NKR) waitlist chain end transplants to other transplants from the NKR and the Scientific Registry of Transplant Recipients between February 2008 and September 2020. Compared to other NKR recipients, chain end recipients were more often older (53 vs. 52 years), black (32% vs. 15%), publicly insured (71% vs. 46%), and spent longer on dialysis (3.0 vs. 1.0 years). Similar differences were noted between chain end recipients and non‐NKR living donor recipients. Black patients received chain end kidneys at a rate approaching that of deceased donor kidneys (32% vs. 34%). Chain end donors were older (52 vs. 44 years) with slightly lower glomerular filtration rates (93 vs. 98 ml/min/1.73 m 2 ) than other NKR donors. Chain end recipients had elevated risk of graft failure and mortality compared to control living donor recipients (both p < .01) but lower graft failure ( p = .03) and mortality ( p < .001) compared to deceased donor recipients. Sharing nondirected donors among a multicenter network may improve the diversity of waitlist patients who benefit from living donation. Abstract : Recipients of chain end living donor kidneys from the National Kidney Registry are similar to recipients of deceased donor kidneys, and chain end donor quality remains high.